Identification of CMS maintainers and restorers for hybrid rice development in Ghana. Issue 5 (3rd September 2018) - Abebrese, Samuel Oppong; Dartey, Paul Kofi Ayirebi; Akromah, Richard; Gracen, Vernon Edward; Offei, Samuel Kwame; Danquah, Eric Yirenkyi
ABSTRACT: The cytoplasmic-genetic male sterility is the most widely used system for hybrid rice ( Oryza sativa ) seed production. It requires three lines: the two hybrid parents (A and R lines) and a third line (maintainer (B line)), which maintains the sterility of the female parent during seed increase. Studies were undertaken to identify maintainers and restorers for introduced cytoplasmic male sterile (CMS) lines using simple sequence repeat (SSR) markers and testcrosses. Molecular screening with SSR marker RM6100 grouped the assembled inbred lines into 30 potential restorers and 55 potential maintainers. One maintainer (WAS 127 -12-1-6-3-1) and 16 restorers were confirmed by testcrosses. WAS 127-12-1-2-3 had higher grain yield per plant in crosses with CMS1 (IR69625A) than the local checks (AgraRice and Jasmine 85) and could be used as a restorer to develop a locally adapted, high-yielding hybrid. Conversion of WAS 127 -12-1-6-3-1 into a local CMS line was stopped because of sterility instability in the BC1 F1 generation. Continued testcrosses to the set of identified potential maintainers could help identify a stable one that can successfully be converted into a locally adapted CMS line.